Enhancing trace acrylamide analysis by bromine derivatization coupled with direct-immersion solid-phase microextraction in drinking water - Li, Mian (Environmental technology, 2021)
Acrylamide is a neurotoxic and genotoxic compound. It is abundant in drinking water because of the usage of polyacrylamide. Its high polarity and small molecular weight characteristics make it difficult to be extracted and analysed. In this study, a novel method was optimized for the determination of trace acrylamide in drinking water. The optimized method, uses bromine derivatization, can avoid false analysis of co-extractives and precursors effectively by transferring acrylamide to 2-bromopropenamide. The 2-bromopropenamide was extracted from water samples using DI-SPME and further analysed by GC-MS. This optimized method uses CAR/PDMS coating SPME fibre to extract at 55°C for 45 min after the addition of 12 g Na2SO4, and then desorbs the extractions in GC injector at 260°C for 3 min. The detection limit was 0.05 μg/L with linearity ranging from 0.5 to 500 μg/L. The repeatability and reproducibility relative standard deviation were 7.30% and 8.50%, respectively. The spiking recovery of tap water samples ranged from 100% to 106%. These results confirmed that this novel method was more precise and accurate than the previously reported SPME methods that used to analyse trace acrylamide in drinking water. The concentrations of acrylamide in the collected samples from clarification and filtration units were 0.80 and 0.71 g/L respectively